Outflow of Human Capital from Punjab: Imperatives and Implications – A Case Study of Sangrur District Punjab State: An analysis of the mass migration of youth from Sangrur District, Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The objective of this research paper is to analyze the reasons and factors responsible for themass migration of the youth from Punjab in general and Sangrur District in particular and its implicationsof the large-scale migration of youth from the villages of Sangrur District to foreign countries. Although, amajority of the youth has migrated to Canada, but some of the youth also have moved to Australia, UK,Germany and other European countries. The young boys and girls have left their native places in searchof fulfilling their dreams and in lure of the dollars which has become a status symbol for the familiesback home. Although, they move overseas for higher education but the main purpose behind theirmigration is their permanent settlement abroad. Punjab has become one of the majorcontributorstowards the economy of these countries because of the influx of Punjabi students enrolledin their collegesuniversities. On an average the annualfeesin Canadian Colleges is in the range of 15 to20 lakh and each year, lakhs of students are migrating to Canada. On the contrary, the enrolment inPunjab colleges is declining very fast and many colleges in Punjab and Sangrur District are facing aheavy crunch for the admission of the students. The youthwho is migrating is very enthusiastic andenergetic and has the potential to contribute effectively towards the upliftment of their native villages,districts, and states, participating significantly in the economic development. It is a cause of concern forany country and state whose human capital is compelled to leave because of a feeling that their owncountry does not offer enough professional opportunities. Even after acquiring high academicqualifications, they have no motivation to stay back. The present paper has been written in the context ofSangrur District of Punjab state, from where thousands of youths migrate every year for better jobs andpermanent settlement overseas. The study remains confined to migration to Canada and Australia.